1998
DOI: 10.1001/archotol.124.5.589
|View full text |Cite
|
Sign up to set email alerts
|

Eating and Weight Changes Following Chemoradiation Therapy for Advanced Head and Neck Cancer

Abstract: Patients undergoing a targeted chemoradiation protocol for head and neck cancer lost about 10% of their pretreatment weight and had a decline in eating ability. Difficulty swallowing during the treatment may be due to adverse effects such as mucositis and nausea. By 18 months after therapy, most were able to eat normally and maintain their weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
2
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 10 publications
7
133
2
5
Order By: Relevance
“…Finally, 15 papers answered all four speciWc criteria with (yes) [13,22,23,27,34,40,42,45,51,52,59,60,65,69,81] (Fig. 1).…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 15 papers answered all four speciWc criteria with (yes) [13,22,23,27,34,40,42,45,51,52,59,60,65,69,81] (Fig. 1).…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Two studies also included patients with unknown primaries [13,52], one also included paranasal sinuses [27], another included thyroid, paranasal sinus, and external ear cancer [81] and one included a group with diverse disease sites (e.g., parotid, ethmoid cavity, and unknown primary) [13,27,51,52,81]. [23,45,59]. In most of the studies, the inclusion criteria were described in detail.…”
Section: General Wndingsmentioning
confidence: 99%
“…While there may be an absence of data specifically relating to the AFRT-CB protocol outcomes at 2 years post-treatment, results from other definitive non-surgical treatment regimens have reported an ongoing functional impact on swallowing and nutrition long-term post-treatment (31)(32)(33)(34)(35). Studies have found that between 5 and 50% of participants are able to tolerate a full diet without restrictions at 1-2 years post-treatment with previously examined radiotherapy protocols for HNC (17, [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The functioning between 1 and 6 months may largely be influenced by xerostomia or fibrosis created by radiotherapy [8][9][10][11] , post-surgical scar formation, and atrophic changes of the free flaps, and in this period, patients were trying to control the new oropharyngeal structure. Because these influences may reduce or become stable after 6 months 9 , the swallowing function more than 6 months post-surgically would be unchanged compared to that at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the post-surgical swallowing function was performed mainly with videofluoroscopic measures [1][2][3][4][5][6] , but some authors use subjective methods such as questionnaires or similar with or without videofluoroscopic measurements [7][8][9][10][11][12] . Pauloski 4 , Wagner 7 To clarify the course of the recovery of post-surgical swallowing dysfunction between 1 and more than 12 months after surgery, and to determine the correlation among videofluoroscopic measures and medical status indicators, post-surgical oropharyngeal swallow efficiency, nutritional condition, type of nutrition, diet levels, and the occurrence of pneumonia were investigated.…”
Section: Introductionmentioning
confidence: 99%